A historicidade dos igarapés: Pintado e Dois de Abril no processo de ocupação territorial de Ji-Paraná em Rondônia (190-2023) - Souza, Patrícia Zandonadi de (2026)
The dissertation text deals with historical aspects of the territorialization of the Rondônia territory, specifically, the urban territory of the city of Ji-Paraná from the study of the Pintado and Dois de Abril streams, between 1970 and 2023. The defined temporality is justified by the fact that it marks the beginning of the population in the municipality of Ji-Paraná in the 1970s and the reflections found in modern times, allowing reflections that substantiate advances and challenges, especially in the hydrography of which the city has in its surroundings. To this end, the investigative question that drove the search for answers was based on: what are the processes of territorialization of the city of Ji-Paraná that occurred with the colonization from the development around the igarapés: Pintado and Dois de Abril? From this ordering, the general objective was to understand the process of territorialization of the city of Ji-Paraná promoted by colonization from the occupation of the space around the streams. The discussions unfold in contextualizing the theoretical debate about the historical territorial occupation around the Pintado and Dois de Abril streams from the 1970s onwards; describe the Pintado and Dois de Abril streams in Ji-Paraná with the history of urbanization between the years 1970 and 2023; to identify the history of the march of the waters, territorialization and urbanization. The methodology used followed the precepts of a qualitative approach, with an exploratory-descriptive objective through documentary analysis and bibliographic survey through the author Burke (2011), about the thematic object. The sources used were interviews with 04 (four) residents who presented information that allowed a retrospective of their arrival in the 1970s, as well as the migratory flow that boosted the population growth in the region, specifically those who were identified as Resident 1, 2 and 3, since Resident 4 arrived in 1998. However, in these results of the interviews, when remembering the igarapés as a place in which the city had an initial point of its growth, the statements also highlight the experience of many citizens, through games, baths, vast waters in quantity, but that there were also signs of degradation due to the shape of the houses in the surroundings, since there was no basic sanitation. A situation that is still present, requiring a revitalization of the space or care with the importance of sanitation and protection, even though there are already movements in search of environmental security, as improvements and even a structure that allows visits and coexistence in the streams are necessary. In addition to these descriptions in the narratives, legal documents, the master plan, photographs, images, cartographies were investigated, having a theoretical debate about the concepts of territory, territorialization, urban history, streams, socio-environmental occupation. In conclusion, through the vision of this researcher,the greatness of propagating this research as a reflexive act, at the same time with the scientific requirements as a warning to society to the detriment of preserving environmental heritage, because the municipality of Ji-Paraná has its historical contributions endorsed by traits that bring their social characterizations, from movements, but also of its waters, in addition the city is surrounded by Amazonian elements that emphasize the numerous streams that make up this environmental scenario, being a priority the creation of public policies aimed at sanitation as measures to safeguard and protect are essential, but in addition, the process of raising awareness of residents, as well as monitoring the Environmental Code of JiParaná.